Out in the cold : science and environment in the history of South Africa’s involvement in the sub-Antarctic and Antarctic in the twentieth century - Van der Watt, Susanna Maria Elizabeth (Lize-Marie) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.